2014
DOI: 10.1002/jnr.23458
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of patients with proteolipid protein 1 gene mutations

Abstract: Pelizaeus-Merzbacher disease (PMD) is an X-linked disorder of the central nervous system (CNS) caused by a wide variety of mutations affecting proteolipid protein 1 (PLP1). We assessed the effects of PLP1 mutations on water diffusion in CNS white matter by using diffusion tensor imaging. Twelve patients with different PLP1 point mutations encompassing a range of clinical phenotypes were analyzed, and the results were compared with a group of 12 age-matched controls. The parallel (λ// ), perpendicular (λ⊥ ), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
1
10
0
3
Order By: Relevance
“…Such MRI is highly representative of children with moderate to severe PMD and demonstrates both the ambiguity and convergence of clinical presentations across people with disparate PLP1 mutations. [54][55][56] To generate a renewable source of PMD-derived cells, we reprogrammed fibroblasts from all 12 individuals to hiPSCs (see Material and Methods). Two independently derived hiPSC lines per individual were ultimately selected for rigorous characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Such MRI is highly representative of children with moderate to severe PMD and demonstrates both the ambiguity and convergence of clinical presentations across people with disparate PLP1 mutations. [54][55][56] To generate a renewable source of PMD-derived cells, we reprogrammed fibroblasts from all 12 individuals to hiPSCs (see Material and Methods). Two independently derived hiPSC lines per individual were ultimately selected for rigorous characterization.…”
Section: Resultsmentioning
confidence: 99%
“…This result was surprising, as infratentorial WM is usually well myelinated on structural MRI in PLP1-related disorders regardless of clinical severity [19]. However, Laukka et al [13] also found changes in MD and RD in the cerebellar peduncle of PMD patients compared to controls. Moreover, infratentorial abnormalities had been described in a DTI study by Hassen et al [22] who found MD, AD, and RD variations in the spinal cord of a SPG2 mouse model.…”
Section: Discussionmentioning
confidence: 72%
“…Laukka et al [13] previously identified increased MD and RD and decreased FA in supratentorial WM regions in 12 PMD patients compared to controls, as expected in hypomyelinating brains. Steenweg et al [21] also found that RD in supratentorial WM was inversely correlated with motor handicap in a cohort of 28 patients with various hypomyelinating disorders.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations